Impact of the Extracellular Vesicles Derived From Trypanosoma cruzi: A Paradox in Host Response and Lipid Metabolism Modulation - D’Avila, Heloisa; Souza, Núbia Pereira de; Albertoni, Ana Luíza da Silva; Campos, Laíris Cunha; Rampinelli, Pollianne Garbero; Correa, José Raimundo; Almeida, Patrícia Elaine de (Frontiers in Cellular and Infection Microbiology, 2021)
Chagas disease is a major public health problem, especially in the South and Central America region. Its incidence is related to poverty and presents a high rate of morbidity and mortality. The pathogenesis of Chagas disease is complex and involves many interactive pathways between the hosts and the Trypanosoma cruzi. Several factors have been implicated in parasite-host interactions, including molecules secreted by infected cells, lipid mediators and most recent, extracellular vesicles (EVs). The EVs of T. cruzi (EVsT) were reported for the first time in the epimastigote forms about 42 years ago. The EVsT are involved in paracrine communication during the infection and can have an important role in the inflammatory modulation and parasite escape mechanism. However, the mechanisms by which EVs employ their pathological effects are not yet understood. The EVsT seem to participate in the activation of macrophages via TLR2 triggering the production of cytokines and a range of other molecules, thus modulating the host immune response which promotes the parasite survival. Moreover, new insights have demonstrated that EVsT induce lipid body formation and PGE2 synthesis in macrophages. This phenomenon is followed by the inhibition of the synthesis of pro-inflammatory cytokines and antigen presentation, causing decreased parasitic molecules and allowing intracellular parasite survival. Therefore, this mini review aims to discuss the role of the EVs from T. cruzi as well as its involvement in the mechanisms that regulate the host immune response in the lipid metabolism and its significance for the Chagas disease pathophysiology.